2022
DOI: 10.3389/fimmu.2022.919402
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nutrition bio-shield superfood powder on immune system function: A clinical trial study among patients with COVID-19

Abstract: The present study aimed to evaluate the effects of Nutrition Bio-shield Superfood (NBS) powder on the immune system function and clinical manifestations in patients with COVID-19. We compare the effects of NBS powder on the immune system function and clinical manifestations among two different groups: 1) intervention group receiving standard treatment scheduled according to treatment guidelines plus NBS powder, and 2) control group receiving only the same standard treatment. The serum levels of IL-2, IL-6, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In a clinical trial conducted by Jalilian et al in Iran, the impact of NBS on immune system function in COVID-19 patients was thoroughly investigated. Their study revealed that the consumption of NBS powder over a duration of 4 weeks yielded a significant influence on the levels of proinflammatory cytokines, particularly interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α), in individuals afflicted with COVID-19 (Azizi Jalilian et al 2022 ). Furthermore, Mosadegh et al conducted a meticulously designed study investigating the impact of NBS superfood on a spectrum of laboratory biomarkers and disease severity in patients afflicted with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a clinical trial conducted by Jalilian et al in Iran, the impact of NBS on immune system function in COVID-19 patients was thoroughly investigated. Their study revealed that the consumption of NBS powder over a duration of 4 weeks yielded a significant influence on the levels of proinflammatory cytokines, particularly interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α), in individuals afflicted with COVID-19 (Azizi Jalilian et al 2022 ). Furthermore, Mosadegh et al conducted a meticulously designed study investigating the impact of NBS superfood on a spectrum of laboratory biomarkers and disease severity in patients afflicted with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), initially documented on December 31, 2019, has been identified as the etiological agent responsible for the onset of the infectious ailment recognized as coronavirus disease 2019 (COVID-19) (Azizi Jalilian et al 2022 ). COVID-19, having disseminated globally, attained the status of a global pandemic as officially declared by the World Health Organization (WHO) on March 11, 2020 (Weidmann et al 2021 ; Oristrell et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies have investigated the effects of multiple nutrition interventions on the prevention or treatment of COVID-19 disease and post-COVID syndrome, and their results were encouraging. [1][2][3] However, concerns have also been raised regarding the risk of bias in current epidemiological studies. 4 Biased results could result in spurious findings or improbably large effect sizes and might ultimately cause harm to patients or end up being research waste.…”
Section: Risk Of Bias In Epidemiological Studies Regarding Nutrition ...mentioning
confidence: 99%
“…Tianyi He 1 Xueting Liu 2 Ruiqi Lv 3 Guo Cheng 3 1 West China School of Medicine, Sichuan University…”
Section: Supporting Informationmentioning
confidence: 99%